The TICking clock of EGFR therapy resistance in glioblastoma: Target Independence or target Compensation - Saleem, Hamza; Kulsoom Abdul, U.; Küçükosmanoglu, Asli; Houweling, Megan; Cornelissen, Fleur M.G.; Heiland, Dieter Henrik; Hegi, Monika E.; Kouwenhoven, Mathilde C.M.; Bailey, David; Würdinger, Tom; Westerman, Bart A. (Drug Resistance Updates, 2019)
Targeted therapy against driver mutations responsible for cancer progression has been shown to be effective in many tumor types. For glioblastoma (GBM), the epidermal growth factor receptor (EGFR) gene is the most frequently mutated oncogenic driver and has therefore been considered an attractive target for therapy. However, so far responses to EGFR-pathway inhibitors have been disappointing. We performed an exhaustive analysis of the mechanisms that might account for therapy resistance against EGFR inhibition. We define two major mechanisms of resistance and propose modalities to overcome them. The first resistance mechanism concerns target independence. In this case, cells have lost expression of the EGFR protein and experience no negative impact of EGFR targeting. Loss of extrachromosomally encoded EGFR as present in double minute DNA is a frequent mechanism for this type of drug resistance. The second mechanism concerns target compensation. In this case, cells will counteract EGFR inhibition by activation of compensatory pathways that render them independent of EGFR signaling. Compensatory pathway candidates are platelet-derived growth factor β (PDGFβ), Insulin-like growth factor 1 (IGFR1) and cMET and their downstream targets, all not commonly mutated at the time of diagnosis alongside EGFR mutation. Given that both mechanisms make cells independent of EGFR expression, other means have to be found to eradicate drug resistant cells. To this end we suggest rational strategies which include the use of multi-target therapies that hit truncation mutations (mechanism 1) or multi-target therapies to co-inhibit compensatory proteins (mechanism 2).
CRIS-Team Scopus Importer:2024-03-07
Keywords: CMET; EGFR inhibition; Glioblastoma; IGFR1; Target compensation; PDGFR; Target independence; Therapy resistance